Nghiên cứu sự tạo phức đơn và đa ligan trong hệ metylthymol xanh (MTX)-Ti(IV)-HX (HX: axit tactric) (H2Tar) (axit xitric)(H3Cit) bằng phương pháp trắc quang và ứng dụng phân tích - Quý và cộng sự, Hồ Viết (Vietnam Journal of Chemistry, 2014)
The first time multiligand complex formation in the system of Methylthymolblue (MTB) Zr(IV)-HX (HX: tartaric acid, citric acid) has been investigated by spectro-photometric method. Complex optimal conditions, composition, mechanism, quantitative parameters of multiligand complexes have been determined. Application possibility of multiligand complexes in analytical chemistry has been considered.